The Incidence and Characteristics of Dermatophytosis in Boarding School Students in Bandar Sei-Kijang, Pelalawan, Riau Province, Indonesia - Maryanti, Esy; Inayah; Enny Lestari; Ade Wirdayanto; Namira, Syafira Nihla; Robiatul Adawiyah (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Indonesia is a tropical country with high humidity and temperatures, making dermatophytosis a persistent health issue. Dermatophytoses are superficial mycoses caused by dermatophytes affecting the skin, hair, and nails. Also known as tinea infections. Purpose: To determine the incidence of dermatophytosis and types of dermatophytosis among boarding school students in Sei-Kijang, Pelalawan, Riau Province. It was conducted from August 2023 until October 2023. Methods:  This research is a simple descriptive study with a cross-sectional design. The aim of the study was to detect dermatophytes in the skin lesions. Dermatophytosis examination was carried out by microscopic examination of skin scrapings with 10-20% potassium hydroxide (KOH) and fungal culture using Sabouraud’s dextrose agar and then examined with a light microscope (lactophenol cotton blue staining). Result: In this study, there were 339 research subjects with 51% male students and 49% female students with an average age of 14.3 years. This study found that the incidence of dermatophytosis was 4.1%, with male students in the 10 to 14-year-old age group having a higher infection rate (71%) than female students. The incidence of tinea corporis was 64.3%, followed by tinea cruris, tinea pedis, and tinea faciei, depending on the type of dermatophytosis. Tinea capitis and tinea unguium were not found. Conclusions: This study demonstrates a high incidence of dermatophytosis, tinea corporis being the predominant type among boarding school students in Bandar Sei-Kijang.